Site Characterization Of Surface And Sub-Surface Spatial Data In Producing Riverbank Filtration Site Suitability Map - Yusoh , Rais (2015)
Remote sensing, Geographic Information System (GIS) and electrical resistivity technique were used in this study to develop the site suitability map for river bank filtration (RBF) locations for a case study in Jenderam Hilir, Dengkil. A high resolution 2012 GeoEye-1 satellite image was classified into six classes using the supervised maximum likelihood classification process. The classified image was further analyzed using GIS technique such as overlaying, buffering and Boolean analysis, to identify the suitability of a RBF location area based on location, distance from the river and distance from built up area. The classified image results show that the overall accuracy is 89% with kappa statistic of 0.864. For the subsurface profile, the electrical images method was used for investigating the aquifer existence and to evaluating the extent of soil subsurface. Electrical-imaging resistivity results showed the lithology of sandy clay to sandy silt sediments at more than 3 m deep. From the inverse model of resistivity variation with depth indicated the occurrence of potential aquifer mostly in silty sand zones within the traps and below it. Based on lithology, a potential water-bearing aquifer was identified at a depth of 3 m depth which is good agreement with interpreted results. A site suitability map was developed and RBF locations were identified. The suitability map also coincides with the existing borehole location at study area.